Diana and Chiron. Bibliographic records on the orphan hero between the Sixteenth and the Seventeenth Centuries (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2022)
This essay focusses on the theme of the “orphaned” hero, or in other words those parts of the poems that deal with characters precociously estranged from their birthplace, who grow up in an alien, when not openly hostile, environment. The following pages explore the fortune of this theme in the 16th-17th century heroic poem.
Keywords: heroic poem; orphaned hero; 16th century; 17th century; Curzio Gonzaga; Francesco Bracciolini; Scipione Errico; Agazio Di Somma; Ascanio Grandi; Girolamo Graziani